Edukasi Tanggap Darurat dan Risiko Bencana Kebakaran di PT Saraswanti Anugerah Makmur Tbk Unit Pabrik Medan - Pasaribu, Donald Frensus; Bukit, Andi Nova; Pakpahan, Evalina; Manalu, Simon Patar Rizki; Azim, Fauzan; Yudha, Tri Kartika; Rahmarisa , Faty (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Urban environments such as Medan City, which recorded 895 fire cases from 2020 to 2023. The main causes of fires include a lack of public understanding of how to extinguish fires and a lack of availability and knowledge of the use of fire extinguishers such as APAR. The purpose of this activity is to provide comprehensive insight and understanding of fires, including fire prevention, handling, and evacuation, the importance of training and education on fire protection, especially in the workplace and residential areas, to minimize the risk of fire and the resulting losses. Method: The activity was carried out at PT. Saraswanti Anugerah Makmur Tbk with 25 participants and the methods used were education by conducting presentations, simulations and training on emergency response education and fire disaster risks. Data collection was carried out through direct observation and evaluation after the training, including an assessment of participants' understanding of the material presented in one meeting consisting of two sessions, namely the first session for 4 hours and the second session lasting 3 hours 45 minutes. Results: Increased knowledge and increased practical skills, namely the use of fire extinguishing equipment including types of fire extinguishers, procedures for using fire extinguishers, understanding of flammable and non-flammable materials and quick response in seeing fire conditions and emergencies by knowing the evacuation layout. Conclusion: The activities carried out have achieved the set targets, with a good level of achievement in increasing community preparedness against fire risks.